Fixed Point of -Hardy-Rogers Contractive Mappings in Partially Ordered Partial Metric Spaces - Mujahid Abbas; Hassen Aydi; Stojan Radenović (International Journal of Mathematics and Mathematical Sciences)
We prove some fixed point theorems for a T-Hardy-Rogers contraction in the setting of partially ordered partial metric spaces. We apply our results to study periodic point problems for such mappings. We also provide examples to illustrate the results presented herein.